College of Engineering Global Ventures - UiTM, UiTM Global (Office of International Affairs (OIA), 2023)
The College of Engineering at UiTM has been actively engaging in international collaborations to foster academic excellence and global partnerships. Here, we highlight some of the key activities with our MoU/MOA partners from recent years.